Anticancer Properties of Eugenol: A Review - Ali T. Zari; Talal A. Zari; Khalid Rehman Hakeem (Molecules, 2021)
Conventional cancer treatments have shown several unfavourable adverse effects, as well as an increase in anticancer drug resistance, which worsens the impending cancer therapy. Thus, the emphasis is currently en route for natural products. There is currently great interest in the natural bioactive components from medicinal plants possessing anticancer characteristics. For example, clove (Syzygium aromaticum L.) (Family Myrtaceae) is a highly prized spice that has been historically utilized as a food preservative and for diverse medical uses. It is reckoned amongst the valued sources of phenolics. It is indigenous to Indonesia but currently is cultivated in various places of the world. Among diverse active components, eugenol, the principal active component of S. aromaticum, has optimistic properties comprising antioxidant, anti-inflammatory, and anticancer actions. Eugenol (4-allyl-2-methoxyphenol) is a musky oil that is mainly obtained from clove. It has long been utilized all over the world as a result of its broad properties like antioxidant, anticancer, anti-inflammatory, and antimicrobial activities. Eugenol continues to pique investigators’ interest because of its multidirectional activities, which suggests it could be used in medications to treat different ailments. Anticancer effects of eugenol are accomplished by various mechanisms like inducing cell death, cell cycle arrest, inhibition of migration, metastasis, and angiogenesis on several cancer cell lines. Besides, eugenol might be utilized as an adjunct remedy for patients who are treated with conventional chemotherapy. This combination leads to a boosted effectiveness with decreased toxicity. The present review focuses on the anticancer properties of eugenol to treat several cancer types and their possible mechanisms.